Improving Tour Package Quotation Efficiency Utilizing The Roundup Function in Microsoft Excel - Muhamad Ari Perdana; Ayu Wanda Febrian (TECHNO: JURNAL PENELITIAN, 2026)
Accurate and efficient tour package quotation or price calculation is one of the key factors in supporting the competitiveness of the travel and tourism industry. Manual calculation processes, which are still widely used in the education and in the travel industries are often time-consuming, prone to errors, and difficult to modify when there are changes in cost components and the number of tourists. This study aims to improve an efficient method for calculating tour package quotations through the utilization of the ROUNDUP function in Microsoft Excel. The method employed in this study is Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that the Excel template based on the ROUNDUP function is capable of simplifying formula structures by up to 60% compared to manual methods, making them easier to modify and reducing calculation processing time. Two Experts validation yielded a score of 90%, categorized as highly feasible. The implementation of this template has proven effective in improving efficiency for accelerating the pricing preparation process and minimizing the risk of pricing calculation errors. Therefore, this tour package quotation template utilizing the round up function can serve as a practical solution for enhancing education and work productivity in the travel and tourism industry.